2017
DOI: 10.18632/oncotarget.19132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the relationship between hepatitis B virus infection and risk of breast cancer: a large sized case-control and single center study in southwest of China

Abstract: PurposeChronic hepatitis C virus (HCV) infection is reported to be associated with early-onset breast cancer, while, as a hepadnavirus, hepatitis B virus(HBV) infection is more common than HCV in China. In this article, it is aimed to study the relationship between HBV infection and risk of breast cancer in China.MethodsThe clinical data of 2452 cases of initially diagnosed breast cancer and 1926 cases of benign breast disease (as controls) with the consecutive reports of HBV serological markers and liver func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In this study, we found that breast cancer patients with hepatitis B surface antibody positivity were more likely to reach bpCR. The mechanism of hepatitis B virus (HBV) and breast cancer progression and prognosis is unclear, but reports have shown that HBV infection is a risk factor for breast cancer 50 . The mechanism may be related to the interference of hepatitis B virus X protein (HBx) on cell repair mechanism, which leads to cell carcinogenesis 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that breast cancer patients with hepatitis B surface antibody positivity were more likely to reach bpCR. The mechanism of hepatitis B virus (HBV) and breast cancer progression and prognosis is unclear, but reports have shown that HBV infection is a risk factor for breast cancer 50 . The mechanism may be related to the interference of hepatitis B virus X protein (HBx) on cell repair mechanism, which leads to cell carcinogenesis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBV infection causes liver dysfunction, which affects estrogen regulation, and estrogen is a known risk factor for breast cancer. Therefore, HBV infection may indirectly induce breast epithelial cells to become cancerous 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al investigated the data of 2452 mammary carcinoma cases and 1926 benign breast disease cases and analyzed reports of HBV serological markers and hepatic function tests, obtained from the Electronic Medical Records of the Breast Cancer Centre of Chongqing in southwest China. They found that the positive rate (8.2%) of HBsAg in breast cancer patients was slightly higher than that (7.8%) in controls ( P > 0.05) . But two other epidemiological studies – one with a much larger sample population – indicated opposite associations.…”
Section: Spontaneous Remission Of Neoplasias Following Acute Hbv Infementioning
confidence: 99%
“…Lu et al 18 Anti-HBs, HBeAg, HBe antibody, and HBcAb). 19 Investigations of the clinical features demonstrated that the axillary lymph node metastases were lower in the case group, as was the ratio of breast cancer patients with pathological T stage ≥T2.…”
Section: Mammary Carcinoma and Hbv Infections Janus Effects Or Insmentioning
confidence: 99%
“… 12–18 Some studies also proposed a hypothetical mechanism for the development of breast cancer as a result of HBV infection: persistence of occult infection and continuous replication of HBV lead to long-term subtle liver damage, and long-term necro-inflammatory damage to the liver may result in persistently high levels of estrogen, which is mainly deactivated in the liver and is a dominant risk factor for breast cancer. 17 , 19 HBV may also directly affect the breast cells through its cis and trans effects of HBx, which may act as oncoprotein. 19 …”
Section: Introductionmentioning
confidence: 99%